HISTORY OF MEDICAL AVIATION IN THE UZBEKISTAN SSR - Tokhtabaev Azamjon Sharipkhojaevich (American Journals, 2022)
This article describes the history of the emergence and development of medical aviation in the Uzbek SSR. It provides detailed information about medical assistance in aviation since the 30s of the 20th century in the history of our country, the mission of medical aviation, the activities of medical aviation, the aircraft used, the established aviation stations, and the reforms carried out in the field.
Keywords: air transport, G. Sedov expedition, medical aviation, medical aircraft, medical aviation stations, evacuation, medical aid